Executive Director's Message - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2016)
Planning started at the close of the 2015 ORNAC Conference and a lot has happened behind the scenes to ensure that the delegate experience delivers great value in continuing education hours, networking opportunities, and industry engagement.